The role of non-covalent intermolecular interactions on the diversity of crystal packing in supramolecular dihalopyridine–silver(i) nitrate complexes. Issue 45 (5th November 2020) - Roca, Sunčica; Hok, Lucija; Vianello, Robert; Borovina, Mladen; Đaković, Marijana; Karanović, Ljiljana; Vikić-Topić, Dražen; Popović, Zora
Abstract : The crystal structures of six novel Ag + complexes with NO3 − and dihalopyridines revealed intriguing differences that were interpreted by DFT calculations. Abstract : Six novel 1 : 2 complexes of silver(i ) nitrate with 2, 5-, 2, 6- and 3, 5-dihalopyridines (halo stands for chlorine and bromine) were prepared by the reaction of an aqueous solution of AgNO3 and the corresponding pyridine derivative in a water–alcohol solution. In spite of having analogous empirical formulae, they reveal intriguing structural differences, except [Ag(NO3 )(2, 5-Cl2 py)2 ] n (1 ) and [Ag(NO3 )(2, 5-Br2 py)2 ] n (4 ), which are isostructural. In contrast, [Ag(NO3 )(3, 5-Cl2 py)2 ]2 (3 ) is dimeric, while its Br analogue [Ag(NO3 )(3, 5-Br2 py)2 ] n (6 ) is polymeric in nature, being the only complex with no halogen⋯halogen interactions. Lastly, both [Ag(NO3 )(2, 6-Cl2 py)2 ] (2 ) and [Ag(NO3 )(2, 6-Br2 py)2 ] (5 ) consist of monomeric molecules, with dissimilar interaction patterns among units linking chains into different 3D structures. In addition, all isolated complexes were identified by elemental analysis and characterized in solution by multinuclear NMR spectroscopy ( 1 H, 13 C, 15 N) and IR and mass spectrometry. DFT calculations verified the predominant tendency of the Ag + ions to bind two pyridine nitrogen atoms and one nitrate ion in their complexes and confirm that their supramolecular structure is a compromise between competing weak intramolecular interactions and steric constrains.